1974
DOI: 10.1111/j.1469-8137.1974.tb02141.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF FLOWERING AND FRUIT FORMATION ON THE SUPPLY OF PHOTOSYNTHETIC ASSIMILATES TO THE NODULES OF PISUM SATIVUM L. IN RELATION TO THE FIXATION OF NITROGEN

Abstract: SUMMARYBoth nitrogenase activity and the accumulation of '^C-labelled photosynthates in the nodules of pea plants in nitrogen-free culture reached maxima shortly before flowering and fruit development. During the period from flowering to fruiting, nitrogenase activity and accumulation of **C-photosynthates in the nodules declined by 60%, whereas the photosynthesis of the plant doubled. Studies of the translocation of the photosynthates within the plant during this period suggested that this might be due to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 14 publications
2
14
1
1
Order By: Relevance
“…Lawrie and Wheeler (1974) found that bract color change can use some of the leaf N content in preparation for anthesis, which might have decreased all sensors readings. All sensors showed quadratic responses across treatments within sampling dates due to sensor readings tendency to plateau at higher N rates, which can be attributed to plants reaching maximum N capacity (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…Lawrie and Wheeler (1974) found that bract color change can use some of the leaf N content in preparation for anthesis, which might have decreased all sensors readings. All sensors showed quadratic responses across treatments within sampling dates due to sensor readings tendency to plateau at higher N rates, which can be attributed to plants reaching maximum N capacity (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…Higher PAR and LA accompanied increased TNA of several forage legumes (3, 4). Floral debudding and the associated promotion of vegetative growth stimulated nodule growth (16) and TNA (11) of pea (Pisum sativum L.). The TNA of soybeans declined after CO2 deprivation (9), shading (10), defoliation (10), stem girdling (9), shoot excision (12), and prolonged darkness (12).…”
mentioning
confidence: 99%
“…The supply of photosynthates to the nodules was showed to be affected by a variety of factors such as; light intensity (3,11), stage of growth (6,7,10), time period of day (12).…”
mentioning
confidence: 99%